2015
DOI: 10.1130/g35515.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term temperature records following the Mw 7.9 Wenchuan (China) earthquake are consistent with low friction

Abstract: Knowledge of the shear stress on a fault during slip is necessary for a physically-based understanding of earthquakes. Borehole temperature measurements inside the fault zone immediately after an earthquake can record the energy dissipated by this stress. In the first Wenchuan Earthquake Fault Zone Scientific Drilling Project hole (Sichuan province, China) we repeatedly measured temperature profiles from 1.3 to 5.3 yr after the 12 May 2008, M w 7.9 Wenchuan earthquake. The previously identified candidate for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 20 publications
5
49
0
Order By: Relevance
“…Drilling has revealed that heat generated by > 50 m of slip during the Tohoku-Oki 2011 earthquake (moment magnitude M w = 9.0) produced only a small temperature anomaly, requiring an average friction coefficient during slip of < 0.1 (ref. 10); similar results were found after the Wenchuan 2008 and Chi-Chi 1999 earthquakes 11,12 . Plate boundary faults must, therefore, be composed of materials that are mechanically weak on long timescales, even if weakness is a transient phenomenon during movement.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Drilling has revealed that heat generated by > 50 m of slip during the Tohoku-Oki 2011 earthquake (moment magnitude M w = 9.0) produced only a small temperature anomaly, requiring an average friction coefficient during slip of < 0.1 (ref. 10); similar results were found after the Wenchuan 2008 and Chi-Chi 1999 earthquakes 11,12 . Plate boundary faults must, therefore, be composed of materials that are mechanically weak on long timescales, even if weakness is a transient phenomenon during movement.…”
supporting
confidence: 63%
“…Drilling studies have taken place in response to earthquakes of M w = 6.9-9.0 in Japan, Taiwan, China and the USA 8,[10][11][12][18][19][20][21] , and the results do not reveal anomalous temperatures or fluid pressures (Fig. 1).…”
mentioning
confidence: 94%
“…Borehole temperature measurements following large events can also help to determine the increase in temperature due to shear heating. The temperature profiles from 1.3 to 5.3 years after the 12 May 2008, M w 7.9 Wenchuan earthquake reveal a maximum temperature increase of 0.2°C [ Li et al , ]. Similarly, the subseafloor temperature observatory in the Japan Trench, following the M w 9 Tohoku‐oki earthquake (2011), has recorded a maximum increase of 0.31°C during the 16 to 25 months after the main shock [ Fulton et al , ], which is consistent with an apparent friction coefficient of 0.08.…”
Section: Possible Causes Of Seismic/postseismic Slip Overlapmentioning
confidence: 78%
“… Geological background of the WFSD‐1 borehole. (a) Geological cross section of the WFSD‐1 drilling borehole and the inferred coseismic slip zone corresponding to the surface rupture [ Li et al ., ]. The cross section, with an orientation of ∼135°, is normal to the strike of the YX‐BC fault.…”
Section: Geological Background and Samplesmentioning
confidence: 99%